Feasibility Investigation of Ipsilateral Reoperations by Thoracoscopy for Major Lung Resection - Sun, Weiyan; Zhang, Lei; Li, Zeyao; Chen, Donglai; Jiang, Gening; Hu, Jian; Chen, Chang (The Thoracic and Cardiovascular Surgeon, 2020)
Background Video-assisted thoracoscopic surgery (VATS) has become the preferred approach for minimizing harm from thoracic operations. There is no report, however, which has discussed the feasibility of VATS in ipsilateral reoperation of major lung resection.Methods The present study included patients who had undergone ipsilateral reoperation of major lung resection by VATS from October 2009 to May 2017. Referring clinical data were recruited for analysis.Results Fourteen patients were recruited in the present study, including nine patients who underwent lobectomy and five who underwent segmentectomy during the second operation. Different hila were found in 6 patients, and pleural adhesions appeared in 10 patients. The average intraoperative blood loss was 203.6 ± 121.7 mL, and the mean operating room time was 2.2 ± 0.5 hours. There were no intraoperative deaths, and only one patient required conversion to thoracotomy. The average drainage time was 5.9 ± 4.6, and the mean hospital stay was 6.7 ± 4.2 days.Conclusion Though it is technically demanding to safely handle the changed hilum structure caused by the last operation, major lung resection by VATS is feasible for ipsilateral reoperation in appropriate candidates.
Keywords: thoracoscopy; major lung resection; hilum; management